2021
DOI: 10.1080/13880209.2021.2013259
|View full text |Cite
|
Sign up to set email alerts
|

Concanavalin A promotes angiogenesis and proliferation in endothelial cells through the Akt/ERK/Cyclin D1 axis

Abstract: Context Concanavalin A (Con A) exhibited multiple roles in cancer cells. However, the role of Con A in endothelial cells was not reported. Objective Our present study investigated the potential angiogenic role of Con A in endothelial cells and ischaemic hind-limb mice. Materials and methods Human umbilical vein endothelial cells and Ea.hy926 cells were employed to determine the effect of Con A (0.3, 1, and 3 μg/mL) or vehicle on angiogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 46 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…These findings open a new insight on the ConA potential as an anti-neoplastic agent that might arise different responses in different cells, whether or not by modulating the same signaling pathways. Therefore, the lectin can even be used as an anti-atherosclerosis agent to repair myocardium in acute MI (myocardial infarction) [ 55 ].…”
Section: Molecular Modulation Of Angiogenesis By Conamentioning
confidence: 99%
“…These findings open a new insight on the ConA potential as an anti-neoplastic agent that might arise different responses in different cells, whether or not by modulating the same signaling pathways. Therefore, the lectin can even be used as an anti-atherosclerosis agent to repair myocardium in acute MI (myocardial infarction) [ 55 ].…”
Section: Molecular Modulation Of Angiogenesis By Conamentioning
confidence: 99%
“…Our results suggest that DGS can stimulate the secretion of VEGFA to upregulate VEGFR2, thereby accentuating the binding of VEGFA to VEGFR2. ERK and Akt are located downstream of the VEGF/VEGFR2 pathway, and it has been shown that the phosphorylation of Erk and Akt can further mediate the proliferation and migration of HUVECs, thereby promoting angiogenesis [46]. The results allude that DGS may promote angiogenesis and vasodilation by promoting the phosphorylation of Akt and Erk.…”
Section: Discussionmentioning
confidence: 74%
“…Through analyzing the KEGG map, Akt, Erk1/2, and BAD were taken into measurement. According to the existing references, LY294002, an inhibitor for the PI3K/Akt signaling pathway, has been confirmed that could also inhibit the phosphorylation of Akt, ERK1/2, and BAD in human or rat cells [65][66][67]. Phosphorylated Akt, Erk1/2, and BAD protein were raised by EPO and suppressed by TNF-α or PI3K/ Akt specific inhibitor-LY294002, denoting that the Akt/ Erk1/2/BAD signaling pathway was activated through phosphorylation.…”
Section: Discussionmentioning
confidence: 92%